ANALISIS YURIDIS MENGENAI PERJANJIAN JUAL BELI YANG DIBUAT MELALUI MEDIA ELEKTRONIK - Rahman, Saidfatur; Sastro, Marlia; Muhibuddin, Muhibuddin (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2025)
The crime of narcotics, regulated in Law Number 35 of 2009 concerning Narcotics, has increased rapidly every year. Women have also participated as perpetrators in narcotics distribution. The urgency of this research is to assess the effectiveness of the implementation of imprisonment with the number of recidivist narcotics prisoners at the Women's Penitentiary Class II A Medan as a benchmark. Additionally, it aims to understand the factors that hinder the effectiveness of imprisonment and the solutions to these issues. This research uses an empirical juridical method with a conceptual approach, is descriptive in nature, and employs data collection techniques through interviews. The results of this study indicate that the implementation of imprisonment for female narcotics offenders is ineffective. This is evidenced by the impact of imprisonment on convicts, particularly in the aspect of initial prevention. The primary factors hindering the effectiveness of imprisonment are economic factors and the suboptimal law enforcement in Indonesia, which contribute to the high number of offenders and recidivists. Externally, societal views and the negative stigma directed at former prisoners can cause them to return to their old environments. Efforts to improve the effectiveness of imprisonment include government measures to ensure the livelihood of the community.